Skythen, Amazonen und Futuristen. Der Steppendiskurs der 1910-1920er Jahre und seine heutigen Implikationen - Marina Dmitrieva (Behemoth : a Journal on Civilisation, 2009)
Due to the archaeological discovery of Greek and Scythian culture in the south of the Russian Empire in the second half of the 19th century and the scientific exploration of Russia’s own Orient – i.e. the non-European peoples of Siberia, Central Asia, Caucasus and middle-Volga – the Eurasian paradigm became more and more influential among Russian intellectuals and artists. For the adherents of Eurasianism, the steppe, broadly considered as a crossroad between Orient and Occident, embodied their concept of the ‘multiethnic imaginary cultural imperial entity’ as its ultimate legitimation. This article investigates the impact of the perception of the steppe on theorists and artists during the decades of the 1910 and 1920.